2020
DOI: 10.21743/pjaec/2020.06.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wastewater Irrigation on Trace Metal Accumulation in Spinach (Spinacia oleracea L.) and Human Health Risk

Abstract: The present research determines the effect of wastewater for irrigation on heavy metal accumulation in vegetables in the example of spinach (Spinacia oleracea L.) and to evaluate human health risk from consumption. Trace metal values of Cd, Cu, Cr, Fe, Zn, Ni and Mn, were determined in the water, soil and plant samples by Atomic Absorption Spectrophotometer. Trace metal concentrations in spinach samples ranged from 0.29 to 0.37, 0.14 to 1.25, 0.07 to 0.67, 1.12 to 2.48, 0.33 to 0.38, 1.92 to 2.90 and 0.51 to 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 24 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…The values of Zn were found within the permissible maximum limits of 200 mg/kg established by USEPA [27]. These Zn values were contradicted as reported by some researchers (12.13 mg/kg) as in October and 8.47 mg/kg in June [28]. However, Kumar and Chopra [25] noticed a higher range of Zn in soil (3.75-4.15 mg/kg).…”
Section: Zinc Content In Watermentioning
confidence: 54%
“…The values of Zn were found within the permissible maximum limits of 200 mg/kg established by USEPA [27]. These Zn values were contradicted as reported by some researchers (12.13 mg/kg) as in October and 8.47 mg/kg in June [28]. However, Kumar and Chopra [25] noticed a higher range of Zn in soil (3.75-4.15 mg/kg).…”
Section: Zinc Content In Watermentioning
confidence: 54%
“…The BCF of Pb is the best way to know the availability of important metals transferred from soil to grown vegetables (Ugulu et al, 2020). The BCF values were less than 1 in all the treatments for the three plant species, which indicated that they were not accumulators of heavy metals in the agroecosystem.…”
Section: Maximum Permissible Limit (Mpl) and Bioconcentration Factor (Bcf) Of Pbmentioning
confidence: 95%
“…The daily intake of HMs was being determined by using the method described previously [28,[34][35][36] through the following equation;…”
Section: Daily Intake Of Metals (Dim)mentioning
confidence: 99%
“…One-way ANOVA was used in SPSS 23 to estimate the significant difference between actions, and the numerical implication was verified at the 0.05, 0.01 and 0.001 levels [34]. Hierarchical cluster analysis was also performed using IBM SPSS 23 software.…”
Section: Statistical Data Analysismentioning
confidence: 99%